Acceptability of low-sodium mozzarella coated with zein and essential oils. Issue 9 (4th June 2020) - Pereira, Lívio Antônio Silva; Bemfeito, Raquel Martino; Bemfeito, Carla Martino; e Silva, Priscila de Castro; Rodrigues, Jéssica Ferreira; Gonçalves, Michelle Carlota; Pinheiro, Ana Carla Marques; Piccoli, Roberta Hilsdorf
Abstract : Purpose: The main purpose of this paper was to evaluate the influence of the zein coating containing essential oils on the sensory characteristics of sodium-reduced mozzarellas. Design/methodology/approach: Mozzarellas were prepared by dipping in brine containing 5, 10, 15 or 20% of NaCl (w/v) that correspond, respectively, to 25, 50, 75 and 100% of NaCl content used in industry. These salted mozzarellas and another one, unsalted, were coated by an edible zein film added with 3% of a mixture of thyme and garlic essential oils (1:1). They were subjected to sensory analysis in relation to salty taste and overall impression. The mozzarella without salt reduction (20% NaCl w/v), coated or uncoated with the edible film, was also subjected to the analysis of water loss and microbiological quality, in order to evaluate the impact of this film on product quality. Findings: The zein coating added with oils did not compromise the sensory acceptance of the mozzarella prepared with up to 50% of salt reduction. Water loss and microbial growth were lower in zein-coated mozzarella than in uncoated mozzarella. These results showed that this film could be applied as natural additive, contributing to the microbiological and sensory characteristics of the mozzarella. Originality/value: This paper contributes to reducing the lack of studies in relation to new technologies for food preservation and sodium reduction. In addition, the zein coating containing essential oils can be tested on other food categories.